Intervening to improve the grade 6 learners’ use of models and strategies in solving addition and subtraction word problems - Kanyane, Mphokane Hellen (My University, 2016)
This research study makes an attempt at intervening in the Grade6learners’ use of models and strategies in solving addition and subtraction word problems based on Realistic Mathematics Education (RME) theory. RME theory advocates for the provision of understandable contexts that learners can relate with to support them in developing models and strategies, with specific reference to the empty number line model in assisting learners to develop an understanding of the structure of number and to work flexibly in solving addition and subtraction word problems. It is in understanding the models and strategies learners are using that we can begin to understand how the learners need to be supported in order to operate at the appropriate mathematics levels for their grade. Participants in this research study, forty boys and girls doing grade six, all with a weaker mathematical background, wrote the same tests in the form of pre test, post test and the delayed post test. After writing the pre test, the learners attended a series of six intervention lessons before writing the post tests. The intervention lessons encouraged learner engagement with word problems and the development of models as representations of problem situations and strategies which represent learner’s manipulation of models in an RME-advocated approach. Learner responses were analysed aiming at the identification of models and strategies they employed, as well as the correctness and success in solving the problems. The analysis found out that mainly there have been some improvements in the repeat sittings from predominantly using the column model with a lot of incorrect answers to using the empty number line with more correct answers. I would therefore encourage the maximum participation of teamwork amongst teachers for identifying and using efficient models and strategies in order to promote performance levels in mathematics through developing an understanding of the structure of number and working flexibly in solving addition and subtraction word problems.
A research report submitted to the Faculty of Science, in partial fulfilment of the requirements for the degree of Master of Science, University of the Witwatersrand. Johannesburg, October 2016.
Keywords: Addition--Study and teaching; Subtraction--Study and teaching; Mathematics--Study and teaching